Innovation Learning Geography with ArcGIS Online: The Impact to Skills Collaborative and Achievement Student School Upper Intermediate - Asmororini, Endah; Kinda, Johanis; Şen, Burcu (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: The aim of this research is to examine the influence of ArcGIS online learning media on collaborative skills and student learning outcomes at State Senior High School 1 Mojo, Kediri Regency.Methodology: The research used a quasi-experimental method with a Post-test only control design. The tool used is ArcGIS online from ESRI. The research population was class 10 students at Mojo 1 High School, Kediri, academic year 2023/2024, with samples selected randomly for the experimental and control classes. Data was collected through observation of collaborative skills and post-test for learning outcomes. Observations were carried out with the help of three observers using a collaborative skills observation instrument based on a Likert scale. Data analysis was carried out using SPSS, including the ANOVA test for homogeneity, the Kolmogorov-Smirnov test for normality, and the T test to test significant differences between the experimental and control classes.Main Findings: The use of ArcGIS online as a learning medium shows a significant increase in collaborative skills and student learning achievement compared to conventional learning media. Post-test and observation results show higher scores in the experimental class.Novelty/Originality of this study: This research introduces the use of ArcGIS online as a geography learning medium, which has not been widely implemented in high schools. This study shows that the use of this technology can significantly improve students' collaborative skills and learning outcomes.
Keywords: ArcGIS Online; Collaborative Skills; Educational Technology; Geographic Education; Learning Outcomes